Vincristine pharmacokinetics pathway and neurotoxicity during early phases of treatment in pediatric acute lymphoblastic leukemia. (May 2016) - Lopez-Lopez, Elixabet; Gutierrez-Camino, Angela; Astigarraga, Itziar; Navajas, Aurora; Echebarria-Barona, Aizpea; Garcia-Miguel, Purificacion; Garcia de Andoin, Nagore; Lobo, Carmen; Guerra-Merino, Isabel; Martin-Guerrero, Idoia; Garcia-Orad, Africa
Aim: Vincristine is an important component of acute lymphoblastic leukemia (ALL) treatment protocols that can cause neurotoxicity. Patients treated with LAL/SHOP protocols often suffer from vincristine-related neurotoxicity in early phases of treatment. Recently, a genome-wide association study connected a SNP in CEP72, involved in vincristine pharmacodynamics, with neurotoxicity during later phases of therapy, which was not replicated during induction phase. These results, together with previous studies indicating that polymorphisms in pharmacokinetic genes are associated with drug toxicity, suggest that changes in the activity or levels of vincristine transporters or metabolizers could work as predictors of vincristine-related neurotoxicity in early phases of treatment in pediatric ALL.Patients & methods: We analyzed 150 SNPs in eight key genes involved in vincristine pharmacokinetics and in 13 miRNAs that regulate them. We studied their correlation with neurotoxicity during induction phase in 152 ALL patients treated with LAL/SHOP protocols.Results: The strongest associations with neurotoxicity were observed for two SNPs in ABCC2 . The genotypes rs3740066 GG and rs12826 GG were associated with increased neurotoxicity.Conclusion: Polymorphisms in ABCC2 could be novel markers for vincristine-related neurotoxicity in pediatric ALL in early phases.